La inteligencia de negocios como una herramienta en la gestión académica -Business intelligence as a tool in academic management - Camargo-Vega, Juan Jose; Joyanes-Aguilar, Luis; Giraldo-Marín, Lillyana María (Revista Científica, 2016)
This paper presents a study, analyze and evaluate characteristics of existing data in the academic community, in order to recommend a model to apply Business Intelligence. It starts from the assumption that knowing the effects on the academic community, if you have a corporate strategy to facilitate decision-making in educational institutions. The results are based on a three dimensional cube, which are combining strong to make decisions with the information made. Finally, we come to different conclusions enabling give sufficient grounds to recommend a model that Integrate Business Intelligence in the academic environment.